RISK FACTORS FOR THE SEVERITY OF ATOPIC DERMATITIS MANIFESTATIONS IN CHILDREN - Belugin, Sergei; Belugina, Olga; Lisowenko, Ekaterina; Belugina, Irina; Aliyeva, Ellada (Journal of the Belarusian State University. Ecology, 2026)
The aim of this study was to identify possible associations of certain somatic, atopic and environmental factors (obtained from medical history) with the severity of atopic dermatitis (AD) measured by the SCORAD index in children undergoing inpatient and outpatient treatment in Minsk. Using a cross-sectional approach, data from 42 patients with a confirmed diagnosis of AD aged 3 to 18 years were analyzed. In each case, AD severity was assessed by the SCORAD index. AD severity in children was directly associated with a short duration of breastfeeding (one-way ANOVA, p < 0,001), a predisposition to allergic reactions (Student’s t-test, p = 0,022), allergic rhinitis (p < 0,001) and reactions to non‑food allergens (p < 0,001). A moderate correlation was found between the SCORAD index and birth weight in boys (r = −0,46, p = 0,043, n = 19), as well as birth length (r = −0,54, p = 0,016, n = 19). In children with AD, the SCORAD score was directly related to the frequency of certain clinical morphological skin manifestations (erythema, edema, oozing, pruritus, lichenification, scaling) and inversely related to remission duration. Reaction to non‑food allergens or a tendency to pustular eruptions were associated with edematous lesions, oozing at eruption sites, excoriations, skin dryness and scaling. Oozing at eruption sites was associated with the absence of breastfeeding or its short duration. The observed protective role of breastfeeding in reducing AD severity and the worsening of AD manifestations associated with adverse environmental factors (nonfood allergens, pustular infection) suggest the need for individualized control of risk factors during patient follow‑up to optimize treatment and prevent AD exacerbations.